AKTIVITAS FISIK BERKORELASI POSITIF DENGAN PERKIRAAN USIA HIDUP PADA ANGGOTA SANGGAR SENAM AEROBIK DI SURABAYA - Kunjung Ashadi, (Arena, 2013)
AKTIVITAS FISIK BERKORELASI POSITIF DENGAN PERKIRAAN USIA HIDUP PADA ANGGOTA SANGGAR SENAM AEROBIK DI SURABAYA   Kunjung Ashadi ABSTRACT Healthy lifestyle has proved giving positive impact for individual alive age. Continuous real practice of healthy lifestyle could increase alive age estimation. A part of healthy lifestyle is sport/physical activity routinely. Based on foreword research result is known that aerobic gymnastics members in Surabaya not yet practicing healthy lifestyle optimally. Pay attention to individual phisical activities/routine level of aerobic gymnastics exercise and linked to healthy lifestyle, so this research is done with hypothesis that (1) there is positive correlation between physical activities and alive age estimation member of aerobic gymnastics studios in Surabaya and (2) there is weak power of correlation between physical activities and alive age estimation member of aerobic gymnastics studios in Surabaya. This research is done at aerobic gymnastics studios in Surabaya with total sample as big as 120 aerobic gymnastics members. Research plan used is observasional with approach cross sectional, data collecting tool is closed inquiry to counts alive age estimation. Data of alive age estimation is analyzed by using Spearman test. Based on research data is known that aerobic gymnastics member has low enough risk of coroner heart sickness, good aspect of healthy lifestyle, medical, security, personality, and psychology, and also moderate aspect of special screening for woman. Based on test result are known significant correlation         (p < 0,05) and weak power of correlation (r = 0,290) between physical activities and alive age estimation member of aerobic gymnastics studios in Surabaya. Conclution of this research result are (1) there is positive correlation between physical activities and alive age estimation member of aerobic gymnastics studios in Surabaya and (2) there is weak power of correlation between physical activities and alive age estimation member of aerobic gymnastics studios in Surabaya. Result of this research is supposed use as basic of next advance research to count alive age estimation in other sex, various sport branch and region in Indonesia. Keywords: lifestyle, alive age, phisical activities, aerobic gymnastics.